Епігенетична адаптація мохів і феномен клітинної пам’яті - Ріпецький, Р.Т.; Хоркавців, Я.Д. (Український ботанічний журнал, 2012)
В условиях постепенного возрастания содержания ртути в субстрате обнаружено селективное действие стрессора на выживание микрорегенерантов клона из отдельной клетки гаметофита мха Tortula modica. Высокий процент выживания (приблизительно треть) свидетельствует об отборе не редкостных, случайных генотипов, а направленных индуцированных эпигенотипов, ”запомнивших“ действие стрессора. Дозирование стрессора дало возможность размежевать физиологическую и эпигенетическую адаптации. У резистентных эпигенотипов активность пероксидазы значительно увеличивалась и расширялся ее электрофоретический спектр, причем одна из молекулярных форм фермента оставалась интенсивнее выраженной у вегетативных потомков на среде без ртути. Различие между физиологической и эпигенетической адаптациями обусловлено, по-видимому, лишь степенью метилированности ДНК и устойчивостью метилированного состояния в регуляторных участках соответствующих генов. Можно предположить, что дозирование стрессора в сравнительном микроклональном анализе дерновинок, сформированных в стрессовых условиях, и дерновинок фоновых локалитетов даст возможность не только обнаружить эпигенетическую адаптацию в природе, но, в известной мере, и предсказать видовой состав мхов при заселении девастированных территорий. Moss clones from individual variably differentiated cells both in the haplo- and diplophase are rather easy to obtain. Under conditions of gradually increased stressor content in the substrate, selective action of mercury on survival of microregenerants of the clone from an individual gametophyte cell of Tortula modica was found. High survival percentage of microregenerants (about one third) could result from selection of the directionally induced, «memorized» stress action epigenotypes, rather than from selection of rare random genotypes. High frequency of epigenetic adaptation is most probably caused by enrichment of DNA, in particular of regulatory regions of many genes, with a substrate of methylation Ї cytosine. Dosing of the stressor enabled to identify the boundary between physiological and epigenetic adaptation. Some increase of peroxidase activity was noted during physiological adaptation of microregenerats to low concentrations of mercury while its selective action hes not been yet expressed. In resistant epigenotypes, the activity of peroxidase increased significantly and the electophoretic spectrum of the enzyme widened, only one molecular form being more clearly expressed in vegetative progenies of epigenotypes on the stressor-free medium. Physiological and epigenetic adaptation types apparently differ only in the overvall level of DNA methylation and stability of the methylated state in regulatory regions of certain genes. Since the delimitation of the two types of adaptation occurs in different mosses under various concentrations of the stressor, its dosing in comparative microclonal analysis of moss turfs under stress conditions and turfs in unstressed localities is supposed not only to reveal epigenetic adaptation in nature but also to predict, to a certain extent, the species composition of mosses populating devastated territories.